CURRENT STATE, PROBLEMS AND PROSPECTS OF THE DEVELOPMENT OF DOMESTIC TRADE OF UKRAINE - SIRENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the state of internal trade of Ukraine. Internal trade of Ukraine, like any developed country, is characterized by rapid dynamics, reaction to changes in the country’s economy, and depends on many factors. The dynamics of domestic trade turnover during 2019-2021 and its structure are shown. The indicator of wholesale turnover increased from 2,322.2 to 3,153.2 billion hryvnias, i.e. by 36%, during the studied period. During the same period, retail turnover increased by 32% - from 793.5 in 2019 to 1044.5 in 2021. In the structure of sold wholesale goods, imported products prevail — from 56.7% in 2019 to 52.4% in 2020 and 54.6% in 2021. The positive balance is maintained at the expense of food products, which were sold for about 90% of domestic production. Taking into account the current state of our country and the fact that a large number of enterprises have stopped their work due to the occupation of the territory or the destruction caused, we can say that the share of imported products will grow. In the structure of sold goods in retail trade, domestic products prevail, especially in the food group, where 80% of goods produced in Ukraine accounted for 2019, 79.4% in 2020, and 77.6% in 2021. In today’s conditions, there is a large number of resellers operating on the market of Ukraine, which differ from each other both in terms of scale of activity and organizational and economic forms, the list of performed functions, specialization, etc. Domestic trade in Ukraine will continue to develop in the direction of forming more effective forms of trade organization. The development of domestic trade is impossible without effective state regulation.